Combined Cerebrospinal Fluid Neurofilament Light Chain Protein and Chitinase-3 Like-1 Levels in Defining Disease Course and Prognosis in Multiple Sclerosis - Gil-Perotin, Sara; Castillo-Villalba, Jessica; Cubas-Nuñez, Laura; Gasque, Raquel; Hervas, David; Gomez-Mateu, Josep; Alcala, Carmen; Perez-Miralles, Francisco; Gascon, Francisco; Dominguez, Jose Andres; Casanova, Bonaventura (Frontiers in Neurology, 2019)
Background: Neurofilament light chain protein (NFL) and chitinase3-like1 (CHI3L1) have gained importance recently as prognostic biomarkers in multiple sclerosis (MS). Objectives: We aimed to investigate NFL and CHI3L1 cerebrospinal fluid (CSF) profiles in multiple sclerosis and the informative and prognostic potential of the individual and combined measures. Methods: CSF NFL and CHI3L1 levels were measured in a cross-sectional cohort of 157 MS patients (99 relapsing-remitting (RRMS), 35 secondary progressive (SPMS), and 23 primary progressive (PPMS)). Clinical relapse and/or gadolinium-enhanced lesions (GEL) in MRI within 90 days from CSF collection by lumbar puncture (LP) were registered and considered as indicators of disease activity. Longitudinal treatment and disability data were evaluated during medical visits with a median follow-up of 50 months. Results: CSF levels of NFL and CHI3L1 were higher in MS patients compared to non-MS controls. In RRMS and SPMS patients increased NFL levels were associated with clinical relapse and gadolinium-enhanced lesions in MRI (p<0.001) while high CHI3L1 levels were characteristic of progressive disease (p=0.01). In RRMS patients, CSF NFL and CHI3L1 levels correlated with each other (r=0.58) and with IgM-oligoclonal bands (p=0.02 and p=0.004, respectively). In addition, CSF CHI3L1 concentration was a predictor for 1-point EDSS worsening (HR = 2.99 (95% CI [1.27, 7.07])) and progression during follow-up (HR = 18 (95% CI [2.31, 141.3])). The pattern of combined measure of biomarkers was useful to discriminate MS phenotypes and to anticipate clinical progression: RRMS presented more frequently high NFL combined with low CHI3L1 levels compared to SPMS (HR 0.41 [0.18-0.82]) and PPMS (HR 0.46 [0.19-0.87]), while elevation of both biomarkers preceded diagnosis of clinical progression in RRMS patients (log rank = 0.02). Conclusions: individual measures of CSF NFL and CHI3L1 are biomarkers of disease activity and progression, respectively. The pattern of combined measure discriminates MS phenotypes. It also predicts the subset of RRMS patients that will progress clinically allowing early intervention.